Optimalisasi Penerapan Kebijakan Penertiban Hewan Ternak Di Desa Oneeha Kecamatan Tanggetada Kabupaten Kolaka - Firdaus; Kartomo; Arafat; Andi Iswan M; Nimrah Rahmayanti Yusuf A; La Ode Asrun Aziz R; Andry Stepahnie Titing; Mutmainnah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem faced in Oneeha Village, Tanggetada District, Kolaka Regency is the low community understanding of Village Regulation Number 4 of 2019 concerning livestock control, which results in frequent crop damage caused by livestock. This community service aims to optimize the implementation of livestock control policies by increasing public understanding and awareness. The method employed was socialization conducted through meetings at the village office with participation from 30 community members and 10 village officials, using pretests and posttests to measure changes in participants’ understanding. The results showed that before socialization, many community members were unaware of the sanction amounts and there was controversy regarding the fines. After socialization, there was a significant increase in community understanding and awareness of the importance of complying with regulations to maintain order and prevent mutual losses. Furthermore, the community and village government proposed evaluating the regulation, which has been in effect for six years, to better suit current conditions. In conclusion, socialization effectively improves community knowledge and supports the harmonization of agricultural and livestock activities, while policy evaluation is necessary for more adaptive and sustainable implementation.